PENGARUH RISIKO KESALAHAN ,AKUNTABILITAS DAN DUE PROFESSIONAL CARE TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI PROVINSI BALI - Adnyani, Ni Kadek Susi; Latrini, Made Yenni (E-Jurnal Akuntansi, 2017)
Quality audits as adherence to professional standards and a contract for conducting the audit. Audit quality can only be produced by a process audit standards that have been defined. The quality audit based on previous research showing that performance is influenced by several factors. This study aims to investigate the influence of the risk of errors, accountability and due professional care to the quality of audits in public accounting in the province of Bali. This research was conducted on a public accounting firm in Bali in 2016. The number of samples taken 60 auditors who are willing to participate in this study. The sample in this research was determined by purposive sampling method. Data were collected using a survey method. Data analysis technique used is multiple linear regression analysis. Based on the analysis, the risk of errors negative effect on audit quality. Accountability positive effect on audit quality. Due professional care positive effect on audit quality.
Keywords: The Risk Of Error, Accountability, Due Professional Care, Quality Audit